Neuromuscular training strategies for preventing lower limb injuries: what's new and what are the practical implications of what we already know? - Hübscher, M.; Refshauge, K. M. (British Journal of Sports Medicine, 2013)
Sports and recreation injuries are now known to be a significant public health problem. Lower limb injuries sustained during childhood and adolescence are associated with increased morbidity, including early development of osteoarthritis and long-term pain and disability;1 ,2 ultimately interfering with work, sports participation and a healthy level of physical activity.